Using social media to promote niche e–commerce projects - M. I. Mohammad Zahir (Путеводитель предпринимателя)
The article is devoted to the study of the effectiveness of using social networks for the development of niche online stores. The relevance of the topic is due to the rapid growth of social commerce in 2023–2025 and the limited advertising resources of small brands. The novelty of the study is expressed in a comprehensive assessment of the impact of interactive content, influence marketing and targeted advertising on customer engagement and conversion, and the strengths of specialization in narrow communities have been highlighted. The work summarizes global statistics on consumer behavior. Particular attention is paid to the behavioral characteristics of Generation Z that generate demand through social media. The goal is to identify the factors that increase the impact of SMM for niche e–commerce projects; the objectives include engagement analysis, comparative analysis of successful cases and the development of practical recommendations. The methods of content analysis of reports, comparative and systematic approach, statistical interpretation of data are used. The research materials contain reports from DataReportal, eMarketer, Statista, publications on the influence economy, article reviews of niche communities and micro–brand fashion, which expands the evidence base for conclusions. The article will be useful for entrepreneurs who want to promote their niche e–commerce projects using social networks and advertising and marketing specialists.